Territorial Management and Governance, Regional Public Policies and their Relationship with Tourism. A Case Study of the Azores Autonomous Region - Castanho, Rui Alexandre (2020)
Bearing in mind the growth in regions with socio-economic bases dependent on tourism, studies that analyze spatial planning processes, regional public policies, and their relationship with tourism activities are essential to achieve the so-desired sustainable territorial development. Through case study research methods, territorial impact analysis, and questionnaires to explore the public perceptions, it was possible to design and implement a study regarding this specific regional governance theme on the Azores Autonomous Region (AAR). The research allowed us to learn that the most a ected activities by public territorial policies in the AAR from the respondents’ perspective were accommodation (54.7%) and nature (51.9%). Conversely, the less a ected were culture (15.1%) and rental/hire services (17.9). Furthermore, it was possible to identify two factors that rule public policies on the growth and development of the Azores: (i) impact in the natural landscape and (ii) suitable production factors.